Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.4049/jimmunol.170.6.2853
|View full text |Cite
|
Sign up to set email alerts
|

Low Activation Threshold As a Mechanism for Ligand-Independent Signaling in Pre-T Cells

Abstract: Pre-TCR complexes are thought to signal in a ligand-independent manner because they are constitutively targeted to lipid rafts. We report that ligand-independent signaling is not a unique capability of the pre-TCR complex. Indeed, the TCRα subunit restores development of pTα-deficient thymocytes to the CD4+CD8+ stage even in the absence of conventional MHC class I and class II ligands. Moreover, we found that pre-TCR and αβTCR complexes exhibit no appreciable difference in their association with lipid rafts, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 44 publications
(61 reference statements)
5
46
1
Order By: Relevance
“…Thus, and in contrast to previously published data [15,17], in preTCR-deficient animals, a differentiation and survival signal emanating from a prematurely expressed HY-TCR appears to be most efficient in the presence of its positively selecting MHC molecules, facilitating optimal transition from DNIII to DNIV.…”
Section: Introductioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Thus, and in contrast to previously published data [15,17], in preTCR-deficient animals, a differentiation and survival signal emanating from a prematurely expressed HY-TCR appears to be most efficient in the presence of its positively selecting MHC molecules, facilitating optimal transition from DNIII to DNIV.…”
Section: Introductioncontrasting
confidence: 95%
“…We performed our analysis in a set-up generated through breeding together the respective alleles, in contrast to the data published so far which had revealed no such requirement. One group had addressed the question of the relevance of TCR-MHC interaction for b-selection through ab TCR by retroviral gene transfer of a pigeon cytochrome C-specific TCRa chain into pTa-deficient fetal thymocytes [17]. Upon organ culture in MHC class I/II-deficient or -proficient thymic lobes, significant progression to the DP stage was observed in both environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pre-TCR requires plasma membrane expression for signaling (O'Shea et al, 1997). DN3 cell membranes are reported to be highly enriched for lipid rafts suggesting an equilibrium shift from elemental to coalescent rafts as a potential mechanism for spontaneous Lck clustering and activation once the ITAMcontaining pre-TCR is expressed (Saint-Ruf et al, 2000;Dykstra et al, 2003;Haks et al, 2003). One study reported constitutive recruitment of Lck and phosphorylation of ZAP-70 in cells expressing a pre-TCR (SaintRuf et al, 2000).…”
Section: Sfk Function During the Dn To Dp Transitionmentioning
confidence: 99%
“…It is thought that pre-TCR signaling in DN cells occurs autonomously in the absence of an extracellular ligand (44). This is in part facilitated by localization in lipid raft domains and by the tendency of pre-TCR␣-chains to dimerize, and perhaps by an inherent difference in the sensitivity of DN cells to respond to low potency signals (33,45,46). Our current data indicate that in addition to the pre-TCR, Lck is also relatively enriched within lipid raft membrane microdomains in DN compared with Lck in total thymocytes.…”
Section: Discussionmentioning
confidence: 99%